Contrast-Enhanced Ultrasound (CEUS) as an Ancillary Imaging Test for Confirmation of Brain Death in an Infant: A Case Report - Slak, Peter; Pušnik, Luka; Plut, Domen (MDPI, 2022)
The practices for determining brain death are based on clinical criteria and vary immensely across countries. Cerebral angiography and perfusion scintigraphy are the most commonly used ancillary imaging tests for brain death confirmation in children; however, they both share similar shortcomings. Hence, contrast-enhanced ultrasound (CEUS) as a relatively inexpensive, easily accessible, and easy-to-perform technique has been proposed as an ancillary imaging test for brain death confirmation. CEUS has established itself as a favourable and widely used diagnostic imaging method in many different areas, but its application in delineating brain pathologies still necessities further validation. Herein, we present a case report of a 1-year-old polytraumatised patient in whom CEUS was applied as an ancillary imaging test for confirmation of brain death. As CEUS has not been validated as an ancillary test for brain death confirmation, the diagnosis was additionally confirmed with cerebral perfusion scintigraphy.